Laparoscopic inguinal hernia repair in children: A single-centre experience over 7 years - Mohan K Abraham; Abdulrasheed A Nasir; Ramakrishnan Puzhankara; Lukman O Abdur-Rahman; Naveen Viswanath; Prashant Kedari; Bindu Sudarshan (Wolters Kluwer Medknow Publications, 2012)
Background: To evaluate 209 consecutive children who underwent laparoscopic hernia repair over a 7-year period. Technical details and clinical results are reported. Materials and Methods: A total of 284 open internal rings were closed laparoscopically in 209 children (142 boys and 67 girls, aged 30 days to 15 years, mean 44 months). One 5-mm and two 3-mm instruments were used to access the peritoneal cavity. A 270° anterolateral peritoneal incision was made. The internal inguinal ring was closed with a nonabsorbable suture. Results: There were no significant intraoperative complications. Length of procedure ranged between 15 and 65 minutes with a mean of 30 minutes. Postoperative hospital stay ranged from 1 to 9 days. Thirty children who presented with a right-sided hernia and 23 with a left hernia (total of 53) were found to have a patent contralateral internal ring on laparoscopy. Mean follow-up was 30 months. There were 2.4% hernia recurrences and cosmesis was excellent. Conclusions: Laparoscopic hernia repair in children can be a routine procedure with increasing experience and better learning curve of surgeons. There is clear visualization of structures and vas remains untouched. The recurrence rate is comparable to that of the traditional open approach with a superior cosmetic result.